FAKTOR RISIKO KEJADIAN GIZI KURANG PADA BALITA DI DESA GAYAMAN KECAMATAN MOJOANYAR MOJOKERTO - Eka Diah Kartiningrum (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Malnutrition in children can cause growth disorders bodies, prone to illness, decreased level of intelligence and mental disturbance and even cause death of the child. Malnutrition can be caused by various factors, among others such as socioeconomic status, knowledge, completeness immunization, infectious diseases, exclusive breastfeeding and early initiation of breastfeeding. The purpose of this research to analyze the risk factors of malnutrition among children under five in the village Gayaman Mojosari Mojokerto. This research used observational analytic research with case - control approach and use 40toddlers as a sample then divided into two groups of samples of 20 infants with malnutrition status as both a case and 20 toddlers with good nutritional status as a control. The independent variable infectious disease history, mother's milk (ASI) exclusive, Early Initiation of Breastfeeding (IMD). The dependent variable is the nutritional status of infants.The relationship between a history of infections, exclusive breastfeeding, IMD and nutritional status were analyzed using logistic regression. The results showed that a history of infectious diseases, exclusive breastfeeding, and IMD influential in determining the incidence of malnutrition among children under five (with R2 of 96.7%). The third variable is a risk factor for the incidence of malnutrition among children under five (infection OR = 1.85; OR ASI = 1.47 and OR IMD = 1.46). Therefore, mothers with babies should have regard to the provision of early initiation of breastfeeding and exclusive breastfeeding the baby and continues to do preventive measures to prevent infections that babies and toddlers can grow with optimal nutritional status